The Effectiveness of School-Based Model of Positive Education Training on the Academic Engagement of Students in Elementary Schools - Sama Sadat; Shahram Vahedi; Eskandar Fathiazar; Rahim Badri Gargari (پژوهش‌های کاربردی روانشناختی, 2020)
The purpose of this study was to determine the effectiveness of the school-based positive education model on the levels of academic engagement of elementary students. The research method was applied in terms of purpose and mixed-exploratory in terms of data collection. The participants were selected from 57 primary schools located in the district one in Tehran. Two schools that both had a six-grade class and included a total of 59 were selected using the multi-stage cluster sampling method, and randomly divided into the experimental (n=28) and control group (n=31). The experimental group received twelve 40-minute sessions of school-based positive education training. Subjects answered the Academic Engagement Questionnaire (Rio and Tsing) before and after the training. The results of analysis of covariance showed that after the intervention in the component of academic engagement, there was a significant increase (p<0.001). Adolescents are advised to use these concepts to improve their academic engagement which prevents dropouts.